QS6: Venous Thromboembolism After Deep Inferior Epigastric Perforator Flap Breast Reconstruction. (July 2021) - Tuaño, Krystle R.; Yang, Jerry H.; Le, Elliot; Colakoglu, Salih; Cohen, Justin B.; Kaoutzanis, Christodoulos; Chong, Tae W.; Mathes, David W.
Abstract : Purpose: Although breast cancer patients undergoing microsurgical breast reconstruction represent a relatively high risk group for venous thromboembolism events, there has been no standardized postoperative prophylactic regimen described to address this problem. An ideal dose of effective antithrombotic therapy that reduces the risk of VTE, while minimizing the cumulative risk of bleeding with on board antiplatelet therapy, is yet to be established. This study is a single-institution review on the rates of VTE following implementation of a postoperative VTE prophylaxis regimen. Methods: A new chemoprophylaxis protocol was introduced starting March 2019 that involved two-weeks of treatment with enoxaparin, regardless of patient risk factors. A retrospective chart review was conducted on all patients who underwent DIEP flap breast reconstruction at our institution between January 2014 and March 2020. Patients were grouped based on whether they enrolled in new VTE protocol in the postoperative period or not. Patient demographics, prophylaxis type and outcomes data were recorded, retrospectively. The primary outcome measure was postoperative VTE incidence. Categorical variables were analyzed with a Chi-Square Test and continuous variables by Student's t-test. Results: A total of 265 patients underwent DIEP flap breast reconstruction between January 2014 and March 2020, of which, 63 (23.8%) patients were discharged with VTE prophylaxis and 202 (76%) patients were discharged without. Patient characteristics were found to be similar between patients before and after the protocol. A total of 9 (3.4%) VTE events were identified, all of which were in the group prior to the protocol. Conclusion: This retrospective study demonstrates successful implementation of a two-week chemoprophylaxis regimen for patients undergoing DIEP flap breast reconstruction. Additional analysis of patient characteristics with VTE at our institution can lead to establishment of a local protocol, with individually tailored prophylaxis regimens. This can further be improved by prospective risk assessment and inclusion of Caprini Score and patient anti-Xa levels in our institution's DIEP flap database.